A regulação penal da exclusão social no tráfigo de seres humanos - Gebrim, Luciana Maibashi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work addresses the topic international trafficking in persons in their relation to the control of migration flows from the clipping of the restrictive migration policies, the criminal expansionist policies and human rights of international migrants. In the current global scenario, new risks go to live with old social problems in a context characterized by rapid, intense and contradictory transformations. The international trafficking resurfaces in contemporary society as a hypercomplex phenomenon, intrinsically related to migration processes, resulting from the combination of several factors, including economic, political, cultural and legal. The influx of poor economic migrants and prostitutes generates fear and insecurity in places of destination and make a noise in the criminal subsystem, which reacts to the stimulus caused by the environment through criminal expansionist policies, focusing on positive general prevention, anticipation of risks and in control groups of the creators of these risks, through the intensification of migration barriers. However, these policies have proven ineffective in combating trafficking in persons, with the aggravating circumstance that vilify the human rights of international migrants. The anticipation too much the risks affects negatively the social field itself regulated, producing a dysfunctional in the criminal system. The dissertation aims to demonstrate this dysfunctionality, from a systemic functional approach, based in autopoietic theory of Niklas Luhmann. For this dissertation, bibliographic and empirical research will draw on. Finally, an attempt is made to sensitize policy makers in order to develop public policies that effectively geared to protecting the human rights of the most vulnerables

Este trabalho aborda o tema tráfico internacional de pessoas em sua relação com o controle dos fluxos migratórios, a partir do recorte das políticas migratórias restritivas, das políticas criminais expansionistas e dos direitos humanos dos migrantes internacionais. No atual cenário global, novos riscos passam a conviver com antigos problemas sociais, em um contexto caracterizado por transformações rápidas, intensas e contraditórias. O tráfico internacional de pessoas ressurge na sociedade contemporânea como um fenômeno hipercomplexo, intrinsecamente relacionado aos processos migratórios, resultante da combinação de diversos fatores, dentre eles, econômico, político, cultural e jurídico. O afluxo de imigrantes econômicos pobres e de prostitutas gera medo e insegurança nos lugares de destino, provocando ruídos no subsistema penal, que reage ao estímulo provocado pelo ambiente, por meio de políticas criminais expansionistas, centradas na prevenção geral positiva, na antecipação de riscos e no controle dos grupos criadores desses riscos, através do recrudescimento de barreiras à migração. Ocorre que tais políticas têm se mostrado ineficazes para combater o tráfico de pessoas, com a agravante de vilipendiar os direitos humanos dos migrantes internacionais. A antecipação demasiada dos riscos afeta negativamente o próprio campo social regulado, produzindo uma disfuncionalidade no subsistema jurídico-penal. A dissertação objetiva demonstrar essa disfuncionalidade, a partir de uma abordagem funcional sistêmica, com aportes na teoria autopoiética de Niklas Luhmann. Para tanto, valer-se-á de pesquisa bibliográfica e empírica. Ao final, intenta-se sensibilizar os formuladores de políticas públicas, a fim de que elaborem políticas efetivamente voltadas à proteção dos direitos humanos dos mais vulneráveis
Keywords: Direito constitucional; Direitos humanos; Tráfico humano - Aspectos jurídicos; Política criminal; Exclusão social; Direitos sociais; Law